Surgical management of the postoperative complications of hepato-pancreato-biliary surgery - Eduardo Javier Houghton; Juan Santiago Rubio (Society of Gastrointestinal Intervention, 2022)
Gastrointestinal surgery is a vast field with many types of procedures, of which hepato-pancreato-biliary (HPB) operations are among the most frequently performed worldwide. Several complications of HPB surgery may occur. Most of these complications, such as wound infection, bleeding, abdominal wall eventrations, and intestinal obstruction, also occur with other procedures. This review analyzes surgical management-related complications associated with HPB surgery, including pancreatic fistula, bile leakage, biliary stenosis, and bile duct damage. Most of the complications of HPB surgery can be managed conservatively or with minimally invasive procedures. Nevertheless, surgical management still plays an important role.